2022
DOI: 10.5114/pjr.2022.123790
|View full text |Cite
|
Sign up to set email alerts
|

Transradial versus transfemoral arterial access in the uterine artery embolization of fibroids

Abstract: Purpose:Transradial arterial access has become more popular in body interventional procedures but has not been ubiquitously adapted. This retrospective study assesses the efficacy of this approach in uterine artery embolization. Aim of the study was to compare transradial to transfemoral arterial access in patients undergoing uterine artery embolization for the treatment of fibroids. Material and methods:A total of 172 patients underwent uterine artery embolization procedures at our institute from October 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Apart from the aforementioned bene ts (i.e. increased patient comfort or faster recovery times), TRA is also associated with a decreased rate of procedural complications when compared to TFA [1][2][3]. This is mostly attributable to the femoral artery being 3x larger in diameter than the radial artery, boding a higher risk for complications such as bleeding, pseudoaneurysm, or AV stula formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the aforementioned bene ts (i.e. increased patient comfort or faster recovery times), TRA is also associated with a decreased rate of procedural complications when compared to TFA [1][2][3]. This is mostly attributable to the femoral artery being 3x larger in diameter than the radial artery, boding a higher risk for complications such as bleeding, pseudoaneurysm, or AV stula formation.…”
Section: Discussionmentioning
confidence: 99%
“…Transradial access (TRA) has gained signi cant popularity over the years in body interventional procedures. Many studies have reported on the bene ts of TRA over transfemoral access (TFA) [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation